New species of caddisflies (Trichoptera: Psychomyiidae, Hydropsychidae, Leptoceridae) from Mekong tributaries, Cambodia - Laudee, Pongsak; Kong, Chamroeun; Malicky, Hans (Zootaxa, 2020)
Males of four new species of caddisflies from Kampong Speu and Siem Reap provinces, Cambodia [Psychomyia kimcheangi n. sp. (Psychomyiidae), Macrostemum siemreapensis n. sp. (Hydropsychidae), Leptocerus angkorwatensis n. sp. (Leptoceridae), and Trichosetodes kampongspeuensis n. sp. (Leptoceridae)] are described and illustrated. Psychomyia kimcheangi n. sp. can be distinguished from other species by characters of the inferior appendages. The main body of each inferior appendage has two branches that are separated near its base but are parallel and close together until the end. In Macrostemum siemreapensis n. sp. the dorsal tip of the phallus has no curved hooklet but instead a knot-like protruding structure in ventral view and looped-like structure in dorsal view. Leptocerus angkorwatensis n. sp. can be distinguished from others by the characters of long needled-like preanal appendages. Trichosetodes kampongspeuensis is distinguished from others by the characters of segment IX in ventral view, which is asymmetrical, and inferior appendages that are not divided and asymmetrical.